The Philosophy of the Metaverse from a Media Perspective (The International Journal for Scientific Research, 2025)
The research aims to understand the concept and philosophy of the metaverse and raises profound questions about this new world that is almost controlling human minds and may extend beyond what can be imagined. The metaverse has its various philosophical dimensions, represented in the nature of reality that will be in light of the metaverse revolution, identity, and different human relationships.The research addresses Metaverse from a media perspective and explains its impact on the current reality, and what will be the future in the coming years under the Metaverse Revolution?The analytical and forward-looking descriptive curriculum was used as one of the approaches suited to the research topic, through the collection of metaverse data, philosophical and informative analysis, description, explanation and interpretation of metaverse-related concepts, disclosure of their future, realistic reading of the present, and prediction of what the future could be under the Metaverse Revolution.The research emphasizes the importance of the metaverse as a technological revolution and an advanced technology that contributes to shaping a more creative future. However, it is essential to understand and train on it to ensure its proper application. Additionally, the metaverse has psychological, social, and ethical implications, necessitating the establishment of laws and regulations aimed at protecting individual rights and data privacy without infringing on freedoms. Furthermore, it is crucial to educate the younger generations about the concept of the metaverse and its potential risks.
Keywords: Metaverse; Metaverse Philosophy; Media perspective; Future of Metaverse.